Reducing the Specular Properties of Metalized Teflon Coverings on Canadian Mobile Servicing Station on the International Space Station - Джейкоб Клейман (Mechanics and Advanced Technologies)
A surface modification process was developed for the metalized Teflon coverings used for thermal protection of electronic equipment on the International Space Station [1]. The developed modification process of Teflon surfaces reduced substantially the specularity of Ag-Inconel coated Teflon thermal control films by changing the morphological appearance of their surfaces by ion-beam texturing in a controlled manner from a metallic-like and shiny to complete milky, white appearance without significantly affecting the thermal optical properties.